Analisis Pengaruh Transaksi Non Tunai Terhadap Peredaran Uang Tunai di Indonesia - Lystia Oktaviyanti Panjaitan; Nurbetty Herlina Sitorus (Publikasi Indonesia, 2022)
This study aims to determine the effect of non-cash payment instruments on cash circulation, analyze variables that affect the decline in cash use in Indonesia such as ATM/debit, credit cards, e-money and mobile banking. This study uses secondary data in the form of time series and the model used in this study is the ECM approach to determine the correlation between ATM/debit cards, credit cards, e-money and digital banking on cash circulation. The results showed that ATM/debit cards have a significant positive effect on cash circulation in the long and short term. In the long and short term credit cards have a significant negative effect on cash circulation. In the long and short term, electronic money has a significant negative effect on cash circulation. Mobile Banking has an insignificant negative effect on cash circulation in the long and short term. Based on the results of statistical tests, the variables of ATM/debit cards, credit cards, e-money, and mobile banking simultaneously affect the circulation of cash in Indonesia.